Evaluation of Sustainable Site Selection Using Analytical Hierarchy Process for Hospitals: Karbala City as A Case Study - Ali Mohammed, Hussein; Neamah Ahmed, Mohammed; J. Alsaad, Aymen (International Journal of Engineering and Technology, 2018)
Site selection for a hospital location is one of the pivotal strategy- related decisions taken by the government. The selection of a suitable site for a hospital requires consideration of multiple alternative solutions and assessment factors. The present study aims at determine the optimum site out of three alternative sites to build a new hospital in Kerbala city. The main sustainability factors are; urban factors (including size, accessibility, restrictions, availability), environmental factors (including geomorphology, hydrology, vegetation, climate, other environmental factors) and economic factors (including service and utilities, cost) factors. The Analytical Hierarchy Process (AHP) as a multi criteria decision support system was adopted to find the weights of each factor and reach to select the most suitable site from three alternative sites. The results showed the site number (2) was the most sustainable site to construct the hospital project, where the alternative site records a biggest normal index of 0.419.